A quantitative comparison of the chemo- and radiotoxicity of uranium at different enrichment grades. (1st October 2019) - Rump, A.; Eder, S.; Lamkowski, A.; Hermann, C.; Abend, M.; Port, M.
Highlights: The heavy metal toxicity of depleted or natural uranium exceeds its radiotoxicity. Lethal amounts of depleted or natural uranium does not cause radiation sickness. However, highly enriched uranium may cause deterministic effects by radiation. Abstract: Objective: The radiotoxic effects of uranium are often in the focus of the public fears but the chemical toxic effects of uranium are reported to surpass radiation effects. As there is no uranium isotope that is not radioactive, it is not possible to study chemical effects fully independently from radiation effects. In order to quantitate and compare radio- and chemotoxicity, we determined the median lethal doses of uranium due to its chemical toxicity and calculated the absorbed radiological doses resulting from the ingestion or inhalation of corresponding amounts depending on the isotopic enrichment grade. Committed effective doses over 50 years are related to the stochastic health effects like cancer occurrence and can be converted to a loss of statistical life time (mean loss 0.4 day / mSv). The equivalent doses absorbed within a short time frame permits conclusion on the induction of deterministic effects (e.g. acute radiation sickness). Method: Simulations were based on the biokinetic models of the International Commission for Radioprotection and performed using Integrated Modules for Bioassay Analysis software. Results were compared with the doses given by the calculator of the WISE uranium project. The fractions of the total doses absorbed within different time periods were derived from the respective areas under the activity-time curves in the whole body. Results: The distribution of the total dose on the organs and tissues depends on the invasion pathway and the solubility of the compound. In the case of inhalation, the absorption of the total dose is more protracted than after ingestion. The incorporation of depleted or natural uranium in lethal amounts due to nephrotoxicity does not lead to deterministic radiation effects and is associated with committed effective doses reaching at most about 200 mSv (proposed possible threshold for therapeutic interventions after accidental radionuclide incorporation). The inhalation of low enriched uranium leads to higher effective doses up to 690 mSv, but they are still insufficient to cause acute deterministic effects. Even highly enriched uranium seems not to induce radiation nephropathy, but deterministic effects on the hematopoetic system cannot be excluded in particularly sensitive patients. But the equivalent doses to the lungs associated with the inhalation of poorly soluble compounds of highly enriched uranium are in a range that may induce radiation pneumonitis. Conclusion: Our findings give clear evidence that for depleted and natural uranium chemical toxicity is much more marked than radiotoxicity. However, this conclusion must not be drawn for enriched and in particular highly enriched compounds that besides stochastic effects may even cause deterministic radiation effects.